Enhanced charge separation at the interface of Cu2O/CuSCN composite thin films synthesized by electrodeposition technique - Seisenbayeva, G.S.; Kambar, D.S.; Zavgorodniy, A.V.; Ilyassov, B.R. (Karagandy University of the name of acad. E.A. Buketov, 2024)
This study focuses on the synthesis and characterization of hole transport layers (HTLs) for solar cells, particularly copper(I) thiocyanate (CuSCN) and cuprous oxide (Cu2O), synthesized via electrodeposition techniques. CuSCN and Cu2O offer promising properties for efficient charge transport in photovoltaic devices. The synthesis processes involve precise control of deposition parameters to achieve desired film morphologies and properties. Characterization techniques including scanning electron microscopy (SEM), atomic force microscopy (AFM), and ultraviolet-visible (UV-Vis) spectroscopy provide insights into film morphology and optical properties. Optimization of synthesis parameters for Cu2O films is explored to enhance their electrical properties. Photoelectric response measurements indicate improved charge separation at the interface of Cu2O/CuSCN composite films. These findings can contribute to the advancement of solar cell technology. Furthermore, the study extends its exploration to the fabrication of Cu2O by electrodeposition at different pH levels. SEM and X-ray diffraction (XRD) analyses reveal the impact of deposition parameters on film morphology and crystal structure, providing valuable insights for tailored synthesis approaches. Overall, this comprehensive study not only advances the understanding of HTL materials synthesis and optimization but also provides valuable guidance for the development of high-efficiency and stable solar cell devices.
Электр тұндыру әдісімен синтезделген Cu2O/CuSCN жұқа композиттік пленкалардың интерфейсіндегі зарядты бөлуді жақсарту
Улучшенное разделение зарядов на границе раздела тонких композитных пленок Cu2O/CuSCN, синтезированных методом электроосаждения
Keywords: solar cells; hole transport layers; electrodeposition; copper(I) thiocyanate; cuprous oxide; optimal synthesis conditions; photoelectric response; chare transport